INDEKS PEMBANGUNAN OLAHRAGA (SPORT DEVELOPMENT INDEX) KABUPATEN FLORES TIMUR - Yohanes Daton Saban (Program Studi Pendidikan Jasmani, STKIP Bina Bangsa Getsempena, 2019)
This research is motivated by problems that have not been known about sports development in East Flores Regency in terms of the Sport Development Index (SDI) aspect. There are four aspects of Sport Development Index that assess a process of sports development in East Flores Regency from year to year which will then influence the measurement of Sport Development Index in the region. The purposes of this study are 1) to determine the level of participation of the East Flores Regency society in exercising 2) to figure out the availability of sports open spaces in East Flores Regency 3) to decide the level of physical fitness possessed by the East Flores Regency community and 4) to find out the quantity and quality of human resources in East Flores Regency. This research is included in the type of evaluation research using quantitative methods. The sample consisted of 180 people consisting of age (7 – 14 years old) 60 people (15 – 24 years old) 60 people and, (25 – 45 years) 60 people. The sampling technique uses stratified random sampling to determine the scope and cluster random sampling to determine respondents. Data collection techniques using questionnaires, a series of Multi Stage Fitness Test protocols and documentation studies. Research data were analyzed using quantitative descriptive data analysis. The results show that (1) the participation index is 0,356, (2) the open space index was 0,394, (3) the Human Resources Index is 0,071 and (4) the fitness index is 0,138 (5). East Flores Regency Sport Development Index (SDI) is 0,239. The conclusion is that the Sport Development Index of East Flores Regency is still in the low category because the total of SDI which includes Participation, Open Space, Human Resource and Physical Fitness of the East Flores Regency inhabitants is 0,239 in the range 0 – 0,499. This means that the development of sports in East Flores Regency still needs to be addressed and concerned by the government and all levels of society so that sports development in East Flores Regency can be more advanced. Abstrak Penelitian ini dilatar belakangi oleh permasalahan yaitu belum diketahuinya pembangunan olahraga di Kabupaten Flores Timur ditinjau dari aspek Sport Development Index (SDI). Ada empat dimensi Sport Development Index yang menilai sebuah proses pembangunan olahraga di Kabupaten Flores Timur dari tahun ke tahun yang selanjutnya akan mempengaruhi pengukuran indeks pembangunan olahraga di daerah. Tujuan penelitian ini adalah 1) untuk mengetahui tingkat partisipasi masyarakat berolahraga Kabupaten Flores Timur dalam melakukan aktifitas olahraga 2) untuk mengetahui ketersediaan ruang terbuka olahraga di Kabupaten Flores Timur 3) untuk mengetahui tingkat kebugaran jasmani yang dimiliki masyarakat Kabupaten Flores Timur dan 4) untuk mengetahui kuantitas dan kualitas sumber daya manusia Kabupaten Flores Timur. Penelitian ini termasuk dalam jenis penelitian evaluasi dengan menggunakan metode kuantitatif. Sampel berjumlah 180 orang yang terdiri dari usia (7-14 tahun) 60 orang (15-24 tahun) 60 orang dan, (25-45 tahun) 60 orang. Teknik pengambilan sampel menggunakan stratified random sampling untuk menentukan wilayah dan cluster random sampling untuk menentukan responden. Teknik pengumpulan data menggunakan angket, serangkaian protokol Multi Stage Fitness Test dan, studi dokumentasi. Data penelitian dianalisis dengan menggunakan analisis data deskriptif kuantitatif. Hasil penelitian menunjukan bahwa (1) Indeks partisipasi 0,356, (2) Indeks ruang terbuka 0,394, (3) Indeks SDM 0,071, dan (4) Indeks kebugaran 0,138 (5). Sport Development Index (SDI) Kabupaten Flores Timur yaitu 0,239. Kesimpulan adalah Sport Development Index Kabupaten Flores Timur masih berada pada kategori rendah karena Indeks total SDI yang meliputi Partisipasi, Ruang Terbuka, SDM dan Kebugaran Jasmani masyarakat Kabupaten Flores Timur sebesar 0,239 berada direntang 0-0,499. Artinya bahwa pembangunan olahraga Kabupaten Flores Timur masih perlu diperhatikan dan dibenahi oleh pemerintahan dan semua lapisan masyarakat agar pembangunan olahraga di Kabupaten Flores Timur bisa lebih maju. Kata Kunci: Sport Development Index